Medical Image Detection with Image Processing Using Machine Learning - Usharani Ghattamaneni, Jaladi Snehalatha (Design Engineering, 2021)
Machine learning algorithms are fundamental aspects of research into medical imaging. A highly flexible approach called deep learning has recently been developed to increase the performance of existing methods of machine learning and overcome previously inflexible problems by using a disorderly technology. Medical imaging is one of the main research areas in which deeper learning can make a significant contribution. This paper describes why convolutional neural processes should be trained and tested and describes existing and potential clinical applications such that they can influence future Neuroradiology. This article provides information around A facility between patients and clinicians with these technologies is essential for connecting and optimizing the significant potential of the new system.